Composition and temporal variation of aquatic insect community (insecta) in Sardineros creek, Verde river drainage, Upper Cauca, Colombia (Revista de Investigaciones Universidad del Quindío, 2010)
We reviewed the composition and variation of aquatic insects from Sardineros Creek, a tributary of Verde river, Quindío river, Upper Cauca, Colombia. 2743 specimens were collected in low rainfall and 1020 during high rainfall. Diptera and Trichoptera were the most abundant. Diversity indices of Shannon-Wiener, Simpson's dominance were low in both climatic periods, while the Margalef richness was high. The index indicated a low diversity as a result of the reduced dissolved oxygen and increased conductivity during the period of high rainfall, which made the declining water quality as good (BMWP/Col: 191) during the low rainfall to acceptable (BMWP/Col: 65) at the high rainfall. Hotelling's T-Squared test probe significative differences between seasons in the community structure (P=0,042, F= 4, 6) and proportion test explain the structure change in 74% of the families analyzed; we propose that seasonality was the variable that most influences in the abundance and diversity of aquatic insects.
Keywords: Seasonality; aquatic ecosystem; macroinvertebrates; biological indicators